2018
DOI: 10.3390/ijms19071990
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning and Expression Analysis of Lactate Dehydrogenase from the Oriental River Prawn Macrobrachium nipponense in Response to Hypoxia

Abstract: Metabolic adaption to hypoxic stress in crustaceans implies a shift from aerobic to anaerobic metabolism. Lactate dehydrogenase (LDH) is a key enzyme in glycolysis in prawns. However, very little is known about the role of LDH in hypoxia inducible factor (HIF) pathways of prawns. In this study, full-length cDNA of LDH (MnLDH) was obtained from the oriental river prawn Macrobrachium nipponense, and was characterized. The full-length cDNA is 2267-bp with an open reading frame of 999 bp coding for a protein of 33… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…CSPs are a critical factor required for cellular adaptation to low temperatures and overcoming the deleterious effects of cold stress [ 94 , 95 ]. Currently, increasing the expression level of CSP at low temperatures has been found in crustaceans such as M. nipponense , C. quadricarinatus , and Alvinocaris longirostris [ 96 , 97 , 98 ]. Similar results were also found in our experiments.…”
Section: Discussionmentioning
confidence: 99%
“…CSPs are a critical factor required for cellular adaptation to low temperatures and overcoming the deleterious effects of cold stress [ 94 , 95 ]. Currently, increasing the expression level of CSP at low temperatures has been found in crustaceans such as M. nipponense , C. quadricarinatus , and Alvinocaris longirostris [ 96 , 97 , 98 ]. Similar results were also found in our experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies in the oriental river prawn confirmed that the glycolytic pathway is regulated by HIF-1α via transcriptional activation of glycolytic enzyme genes in prawn muscle tissue in response to hypoxia, including LDH and HK ( 55 , 56 ). Furthermore, the present study confirmed that the GLUT1 promoter contains an HIF-1α-binding HRE using ChIP.…”
Section: Discussionmentioning
confidence: 64%
“…Similarly, we constructed plasmids pGL3-GLUT2-1, pGL3-GLUT2-2, and pGL3-GLUT2-3. The protocols detailed in a previous study were used for the luciferase assay and transfection experiments under normoxic and hypoxic conditions ( 56 ). Briefly, the pGL3-reporter plasmids containing one copy of each potential HRE site were transfected into hemocytes using the X-trem-eGENE HP DNA transfection reagent (Roche).…”
Section: Methodsmentioning
confidence: 99%
“…Currently, SNP studies in aquatic animals have predominantly focused on growth traits; previous studies successfully identified growth-related SNP loci in several shrimp species, including M. japonicus [ 33 ], M. rosenbergii [ 34 ], and Litopenaeus vannamei [ 35 ]. Previous studies also reported that lactate dehydrogenase [ 36 ], glutathione peroxidase [ 37 ], p53 [ 38 ], GST [ 9 ], and caspase-3 [ 39 ] were involved in hypoxia tolerance in M. nipponense . GST-2 is an important detoxification enzyme, with key roles in responses to hypoxia [ 40 ].…”
Section: Discussionmentioning
confidence: 99%